Fluorescence imaging of selenol in HepG2 cell apoptosis induced by Na2SeO3. Issue 15 (19th January 2015) - Kong, Fanpeng; Hu, Bo; Gao, Yan; Xu, Kehua; Pan, Xiaohong; Huang, Fang; Zheng, Qiuling; Chen, Hao; Tang, Bo
Abstract : In order to investigate the Na2 SeO3 anticancer mechanism in HepG2 cells, a novel selenol fluorescence probe has been designed and used to image selenocysteine (Sec) in living cells and in vivo. Abstract : A novel fluorescence probe (HB) has been designed and synthesized to image selenol in living cells and in vivo for the first time, and used to investigate the Na2 SeO3 anticancer mechanism in HepG2 cells.